The influences of environmental awareness on green performance - M.H. Mansour (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Despite the various environmental challenges the hotel sector faces, there is a significant need to resolve them by applying sustainable techniques like green human resource management. As a result, there is a pressing need to investigate how green human resource management may improve environmental performance. This study investigates the causal linkage among environmental awareness, green human resource management, green behaviours, green performance, and servant leadership.METHODS: The data were collected via Questionnaires obtained from employees working in hotels in Amman, Jordan (52.5 per cent response rate). To evaluate the model, Smart Partial Least Square was employed to conduct validity and reliability testing and develop structural equation modeling.FINDINGS: According to the results, Environmental awareness mediated the effects of green human resource management and green behaviours on green performance. Green HRM was found to have a direct and substantial impact on Green Performance (β = 0.109, p < 0.005). A positive and statistically significant relationship between Green Behaviors and Green Performance was also found (β = 0.338, p < 0.000). Additionally, Green HRM has a favorable and significant effect on Environmental Awareness (β = 0.176, p < 0.0001). Furthermore, Environmental Awareness is positively and significantly influenced by Green Behaviors (β = 0.743, p < 0.000). Green performance positively relates to environmental consciousness (β = 0.186, p < 0.000).CONCLUSION: Based on social cognition, social exchange, and social learning theory, this study contains theoretical insights, practical implications, and positive recommendations for hospitality managers and scholars. Current research is critical because it emphasizes environmental stewardship in industries that directly connect to and influence the environment, such as tourism and hospitality. The study does not examine environmental performance and behavior in general but instead evaluates pro-environmental behaviors in depth by considering green behaviour.